Galería virtual para difundir el patrimonio de la cultura Puruhá del Museo Arqueológico Paquita de Jaramillo por medio del diseño 3d - Espinoza Montalvo, Estefania Alexandra (2021)
The Archaeological Museum "Parquita de Jaramillo" has a vast collection of archaeological pieces of various cultures and dates, unfortunately the population of Riobamba and the general public lack interest in them. For this reason we saw the need to disseminate the existing heritage in the museum starting with the Puruhá culture to create interest in their pieces by developing a 3D virtual gallery, which includes three-dimensional models of 11 archaeological pieces of that culture, plus a virtual tour of the museum in 3D, presenting a new and better way to visualize the archaeological pieces. The methodologies chosen were Design Thinking and 3D (Blender), which follow a structure that should be taken into account as they worked hand in hand for the realization of the project, as one complements the other as in the production that complements it with the phases of empathizes, defines and idea and prototyping complemented by the production of the project. Likewise, information about the museum and its archaeological cultural heritage can be found, as well as concepts necessary for the development of the research project.